The state of the myocardial nitrooxidergic system during modelling of doxorubicin-induced chronic heart failure and the administration of βeta-blockers of various generations - Belenichev, I. F.; Goncharov, O. V.; Abramov, A. V.; Kucherenko, L. I.; Bukhtiyarova, N. V.; Makyeyeva, L. V.; Ryzhenko, V. P.; Semenov, D. M.; Бєленічев, Ігор Федорович; Гончаров, О. В.; Абрамов, Андрій Володимирович; Кучеренко, Людмила Іванівна; et al. (My University, 2024)
In this study, a 1-(β-phenylethyl)-4-amino-1,2,4-triazolium bromide (Hypertril) with β-blocker and NO-mimetic properties, which is of interest for the treatment of chronic heart failure (CHF) was examined. The purpose was to study the effect of various β-blockers on the indicators of the NO system in a CHF model. CHF was induced with doxorubicin at a cumulative dose of 14 mg/kg in 85 Wistar rats, which were intragastrically administered metoprolol succinate (15 mg/kg), carvedilol (50 mg/kg), bisoprolol (10 mg/kg), nebivolol (10 mg/kg) and Hypertril (3.5 mg/kg). In the heart, the expression of eNOS and iNOS and the concentration of stable metabolites NO, nitrotyrosine and SH groups were determined. Modelling of CHF leads to a decrease in the expression of eNOS and an increase in iNOS and nitrotyrosine, as well as a deficiency of NO and the SH group. Nebivolol, especially Hypertril, had the most pronounced normalising effect on the NO system. The advantage of Hypertril over basic β-blockers was revealed.
Keywords: chronic heart failure; Hypertril; 1-(β-phenylethyl)-4-amino-1,2,4-triazolium bromide; nitric oxide system markers